A graduate course in algebra - Farmakis, Ioannis; Moskowitz, Martin A. (World Scientific, 2017)
This comprehensive two-volume book deals with algebra, broadly conceived. Volume 1 (Chapters 1-6) comprises material for a first year graduate course in algebra, offering the instructor a number of options in designing such a course. Volume 1, provides as well all essential material that students need to prepare for the qualifying exam in algebra